Incidência clínica de fratura de limas endodônticas de níquel-titânio acionadas em cinemática rotatória contínua versus cinemática reciprocante : uma revisão sistemática e meta-regressão - Vieira, Rosângela Mello (2018)
Introduction: The fracture of nickel titanium endodontic instruments may have a negative impact on the prognosis of the treatment, mainly because it blocks or prevents access to the root canal system in all its extension, compromising its modeling and sanification. Results from in vitro studies suggest that reciprocating motion can reduce the risks of torsion fracture and cyclic fatigue of NiTi instruments, compared to the continuous rotation movement. However, most of the studies that evaluate fracture resistance of instruments in reciprocating and rotational motion are in vitro studies, the generation of evidence of which is limited in comparison to the level of evidence generated by clinical studies in humans. Therefore, the present systematic review investigated whether the available evidence supports the hypothesis that reciprocating motion results in a lower clinical incidence of NiTi limb fracture as compared to rotational kinematics. Methodology: The PubMed, Embase, Isi Web of Science and Cochrane Library databases were searched until August 2017, without language restriction. In addition to the electronic searches, manual searches were made for additional references in specific chapters of relevant books in the area and also search in the gray literature. Based on the inclusion and exclusion criteria, two reviewers independently assessed the quality of each study based on the NewCastle Ottawa scale. The main exposure variable was the type of kinematics used to prepare the root canal (continuous or reciprocating) and the primary outcome variable was determined by the incidence of fracture of NiTi instruments in endodontic treatments. The incidence of fracture was recorded, having as unit of analysis: patients, teeth, instruments or channels. Other confounding variables collected included: country, year of publication, study design, type of system, group of teeth, number of sessions, operator and number of uses of NiTi instruments. The sources of heterogeneity were explored and the bi and multivariate meta logistic regression were performed to calculate the pooled estimates - odds ratios (OR) and 95% CI - for the incidence of instrument fracture, assessing the role of primary exposure and co- as moderators of the outcome. Results: Among the 737 articles initially identified, after the duplicates were removed, 39 comprised the final quantitative analysis, of which 32 reported the use of continuous rotation and 7 the use of reciprocating kinematics. Thirty-seven studies were included in the meta regression (N = 48,405 instruments). The aggregate clinical incidence of fracture of NiTi files was 2.43%, being 2.62% for continuous rotational movement and 0.4% for reciprocating kinematics. In the bivariate analysis, continuous rotational motion showed a greater incidence of fracture in relation to the reciprocating kinematics (OR = 6.39, 95% CI = 1.10-36.9), and the other associated covariates (p <0.05) with the incidence of fracture were: year of publication, operator and number of uses of the instruments. The multivariate models revealed that the number of uses of NiTi files in> 1 tooth (OR = 6.46, 95% CI = 1.42-29.3) and that general clinical operators (OR = 11.8, 95% CI = 1.49-93.5) were independently associated with a higher incidence of fracture of NiTi files, whereas kinematics was non-significant (OR = 1.56, 95% CI= 0.24-10, 0) after the settings. Conclusions: Available evidence from observational studies is limited but consistent, suggesting that reciprocating kinematics is associated with a lower incidence of fracture of NiTi files when compared to continuous rotation. In addition, the results revealed that other related clinical factors to the abilities of the operator,to the number of uses of the NiTi instruments, and to the advances in alloy composition as well as in the design of the files, have proved to be more relevant factors for fracture prevention than the type of kinematics employed.